2021
DOI: 10.1097/corr.0000000000001970
|View full text |Cite
|
Sign up to set email alerts
|

Are Knotted or Knotless Techniques Better for Reconstruction of Full-Thickness Tears of the Superior Portion of the Subscapularis Tendon? A Study in Cadavers

Abstract: BackgroundKnotted and knotless single-anchor reconstruction techniques are frequently performed to reconstruct full-thickness tears of the upper portion of subscapularis tendon. However, it is unclear whether one technique is superior to the other.Questions/purposes(1) When comparing knotless and knotted single-anchor reconstruction techniques in full-thickness tears of the upper subscapularis tendon, is there a difference in stiffness under cyclic load? (2) Are there differences in cyclic gapping between knot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Three studies 28 , 32 , 33 used the Fox-Romeo 34 classification system to recreate type II (complete tear of the upper 25%) and III (complete tear of the upper 50%) tears of the subscapularis, 1 study 31 used the Lafosse classification 8 to recreate type II tears (complete tear of the upper 1/3), and 2 studies created complete full-thickness tears 29 , 30 ( Table 2 ). Of the included studies, two 28 , 29 compared single-row and double-row repair, one 30 compared single-row to transosseous repair, and 3 studies 31 , 32 , 33 used only single-row suture anchor constructs. Two studies compared knotted and knotless single-row repairs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies 28 , 32 , 33 used the Fox-Romeo 34 classification system to recreate type II (complete tear of the upper 25%) and III (complete tear of the upper 50%) tears of the subscapularis, 1 study 31 used the Lafosse classification 8 to recreate type II tears (complete tear of the upper 1/3), and 2 studies created complete full-thickness tears 29 , 30 ( Table 2 ). Of the included studies, two 28 , 29 compared single-row and double-row repair, one 30 compared single-row to transosseous repair, and 3 studies 31 , 32 , 33 used only single-row suture anchor constructs. Two studies compared knotted and knotless single-row repairs.…”
Section: Resultsmentioning
confidence: 99%
“…Single-row repair in the current review used either 1 or 2 double-loaded suture anchors and were knotless or tied with variations of mattress or modified Mason-Allen stitches. Sgroi et al 32 compared knotted and knotless single-row repair for Fox-Romeo III subscapularis tears and found no significant differences in biomechanical properties for both constructs. Likewise, Borbas et al 31 compared 3 different single-row constructs (knotted lasso-loop mattress, knotted mattress, and knotless suture tape) for Lafosse II subscapularis tears and found that the constructs resulted in similar ultimate load, gap formation, and stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations